Penerapan Budaya Religius dan Dampaknya Terhadap Kecerdasan Spiritual Peserta Didik di SDN 35/VI Seling Kabupaten Merangin Jambi - Nila Nurul Afifah; Yulia Rahman; Jasmienti Jasmienti; Nurhasnah Nurhasnah (Simpati, 2023)
This research was structured with the aim of knowing the application of religious culture, and the impact of the application of religious culture on the spiritual intelligence of students, as well as to find out the inhibiting and supporting factors in the application of religious culture at SDN 35/VI Seling Kab, Merangin, Jambi. This type of research is qualitative research. Data sources who are key informants are students, and supporting informants are educators. Data was collected through using observation, documentation and interviews. The results showed that the forms of the application of the religious culture of students at SDN 35/VI Seling were congregational prayers, the culture of tadarus Al-Qur'an and prayer together, Istighosah and Asmaul Husna, mutual respect and tolerance, Islamic school dress code, smiles, greetings and greetings (3S), disciplined school members, school members who take care of the beauty of themselves, the room and the school environment, Islamic boarding schools, commemoration of Islamic holidays. The impact of applying religious culture to the spiritual intelligence of students is the midday prayer in congregation and the Islamic way of dressing trains students to feel the presence of Allah, congregational prayers, istighosah and asmaul husna trains students to get used to always remembering and praying to Allah, Tadarus Al-Qur'an makes the habit of reading Al-Qur'an students increasing. Mutual respect and tolerance makes students tend to be good, mutual respect and tolerance at school makes students treat people well and like to help others. The supporting and inhibiting factors for the application of students' religious culture are from the school principal, educators, students, from the community and parents, as well as facilities and infrastructure.